2018
DOI: 10.1007/978-3-030-04200-4_27
|View full text |Cite
|
Sign up to set email alerts
|

A Nonlinear Autoregressive Distributed Lag (NARDL) Analysis on the Determinants of Vietnam’s Stock Market

Abstract: This study examines the impacts of some macroeconomic factors, including exchange rate, interest rate, money supply and inflation, on a major stock index of Vietnam (VNIndex) by utilizing monthly data from April, 2001 to October, 2017 and employing Non-linear Autoregressive Distributed Lag (NARDL) approach introduced by Shin et al. [33] to investigate the asymmetric effects of the aforementioned variables. The bound test verifies asymmetric cointegration among the variables, thus the long-run asymmetric influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Le Phong et al (2019) examined the impact of some macroeconomic factors such as exchange rate, interest rate and money supply on the Vietnam stock market index using monthly data from 2001 to 2017 and the NARDL approach introduced by Shin et al (2014). The model indicates the asymmetric impact of money supply and interest rate on the index return.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Le Phong et al (2019) examined the impact of some macroeconomic factors such as exchange rate, interest rate and money supply on the Vietnam stock market index using monthly data from 2001 to 2017 and the NARDL approach introduced by Shin et al (2014). The model indicates the asymmetric impact of money supply and interest rate on the index return.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The hypothesis that macroeconomic policies significantly affect stock market returns is of great interest among many academics and practitioners. Le Phong et al (2019) used non-linear ARDL approach to indicate the significant asymmetrical effects of money supply, interest rate and inflation on VNIndex (the market index of Vietnam). They found that in the short-run, the effect of the positive components is substantially higher than the negative components, but they demonstrated the opposite in the long-run.…”
Section: Introductionmentioning
confidence: 99%
“…The brief discussion on Table-5 demands an in-depth investigation to find out hidden association between variables, as this can be further tested by using ARDL (uni-directional) and NARDL (bi-directional) frame to address asymmetries. For better predictions, the results of bi-directional causality & low values of adjusted R 2 , must be investigated into its POS & NEG partial sums of decomposition of variables to enhance the predictive power of selected components of GI and to develop graphical asymmetric multipliers for cumulative dynamics called AMCD graphs (Allen & McAleer, 2020;Okere, Muoneke, & Onuoha, 2021;Phong, Van, & Bao, 2019).…”
Section: Results Of Pair-wise Granger Causalitymentioning
confidence: 99%
“…The convergence rate (SOA), in case of NARDL, is worth-mentioning, 64.02% Per Annum compared to 32.34% per annum convergence rate in case of ARDL. Hence, NARDL has better predictive power accordingly (K. Ahmed et al, 2021;Bist, 2017;Phong et al, 2019;Shin, Yu, & Greenwood-Nimmo, 2012).…”
Section: Table 9: Diagnostic Inspection For Gi and Smd Of Pakistanmentioning
confidence: 99%
“…Lastly, the validity and reliability of the NARDL model has been established through different work from different authors for example in the analysis of the FTSE and S & P 500 indexes, the determinants of crude oil prices and in the determinant of Vietnam's stock market (Allen, & McAleer, 2021;Salem, Nouira, Jeguirim & Rault, 2022;Phong, Van & Bao, 2019) respectively.…”
Section: Dynamic Effect Interpretationmentioning
confidence: 99%